Existence and multiplicity of solutions for asymptotically linear Schrödinger–Kirchhoff equations. (December 2015) - Wu, Yue; Liu, Shibo
Abstract: The purpose of this work is to study a Schrödinger–Kirchhoff equation in R 3 with the nonlinearity asymptotically linear and the potential indefinite in sign. By variational methods, we obtain the existence of multiple nontrivial solutions for this problem.